The need for vigilance in extended criteria donors with a past history of malignancy: a case report and review of literature - Nickkholgh, Arash; Frey, Erich; Krenzel, Christoph; Lauchart, Werner; Flechtenmacher, Christa; Schmidt, Jan; Schemmer, Peter (Annals of transplantation, 2011)
BACKGROUND: Organ shortage has prompted many transplant centers to extend their criteria for organ acceptance including the history of a variety of co-morbidities in donors. The use of organs from donors with a past medical history of malignancy in order to reduce the waiting list mortalities remains a dilemma. - CASE REPORT: Herein we report a 62-year-old female donor with a history of a presumably cured serous adenocarcinoma of the ovary and underscore the need for vigilance in the search of an active site of cancer while assessing these donors for organ recovery. - CONCLUSIONS: In order to minimize the risk of donor tumor transmission, especially in the donors with a past medical history of cancer, extensive evaluation of the donor including the surgical exploration of all body cavities is absolutely necessary. Any suspicious lesion should prompt a frozen section biopsy. In this regard, an on-call pathologist to do the frozen section should be an integral part of the transplant team.
Gesehen am 22.09.2022